The Revolution Within the Revolution : Workers' Control in Rural Portugal - Bermeo, Nancy Gina, 1951- (Book collections on Project MUSE., 1986)
In this dramatic story of the making and unmaking of Portugal's agrarian reform, Nancy Bermeo probes the origins and effects of the workers' actions. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.